KONTEKSTUALISASI SUFISME BAGI MASYARAKAT URBAN - Rubaidi, Rubaidi (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2019)
This paper critically examines the important roles of the presence of Sufism institutions for the urban middle class. Writing taken from research on the Majelis Shalawat Muhammad in Surabaya and Bojonegoro presents constructive thinking as well as the creative practices of the murshid, Gus Kahar and Gus Mustakim. Both managed to